2010
DOI: 10.1073/pnas.1004139107
|View full text |Cite
|
Sign up to set email alerts
|

Long-range function of an intergenic retrotransposon

Abstract: Retrotransposons including endogenous retroviruses and their solitary long terminal repeats (LTRs) compose >40% of the human genome. Many of them are located in intergenic regions far from genes. Whether these intergenic retrotransposons serve beneficial host functions is not known. Here we show that an LTR retrotransposon of ERV-9 human endogenous retrovirus located 40-70 kb upstream of the human fetal γ-and adult β-globin genes serves a long-range, host function. The ERV-9 LTR contains multiple CCAAT and GAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 38 publications
(44 reference statements)
2
84
0
Order By: Relevance
“…Although there are well-characterized examples of cis-acting regulatory regions restricted to particular mammalian lineages (e.g. [28,29]), several diseaseassociated mutations mapping to non-coding regions in humans have turned out to reside within phylogenetically conserved enhancers [6,30 -36].…”
Section: (A) Enhancer Evolution In Vertebratesmentioning
confidence: 99%
“…Although there are well-characterized examples of cis-acting regulatory regions restricted to particular mammalian lineages (e.g. [28,29]), several diseaseassociated mutations mapping to non-coding regions in humans have turned out to reside within phylogenetically conserved enhancers [6,30 -36].…”
Section: (A) Enhancer Evolution In Vertebratesmentioning
confidence: 99%
“…23 The ERV-9 LTR enhancer complex is active in stem/progenitor cells including erythroid progenitor cells; 34,35 it initiates synthesis of ERV-9 lncRNAs from the 5 0 end of the R region through the U5 region into the downstream genomic DNA to activate transcription of the globin genes by a long-range tracking and transcription mechanism. 36,37 In the current study, we found that the transcriptionally active ERV-9 LTR was >90% hypermethylated in erythroleukemia K562 cell line and primary human erythroblasts cultured from peripheral blood CD34C cells. Deletion of the ERV-9 LTR in K562 cells by CRISPR-Cas9 demonstrated that the hypermethylated ERV-9 LTR possessed in vivo function and activated transcription of the downstream globin genes.…”
Section: Introductionmentioning
confidence: 84%
“…In CGI-1 probe, the CCAAT motif did not bind NF-Y, potentially because the 3 0 flanking bases of the CCAAT core were not conducive to NF-Y binding 37,61 ; for yet unknown reasons, the E box motif (CACTTG) did not bind any of the E box binding TFs (USF1, 2, c-Myc, and c-Myb) (Fig. 5d, lanes 2-4, 7-8).…”
Section: In Vivomentioning
confidence: 99%
See 2 more Smart Citations